1997
DOI: 10.1021/ic9604728
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Absorption Spectroscopy of a Neodymium(III) Complex with Triethylenetetraaminehexaacetic Acid, Na3[Nd(TTHA)]·2.5NaClO4·7.617H2O

Abstract: The crystal structure and absorption spectroscopy results of the Na(3)[Nd(TTHA)].2.5NaClO(4).7.617H(2)O compound are presented. The crystal structure of the complex was determined by X-ray analysis. Crystals are monoclinic, space group C2/c, with a = 38.446(8) Å, b = 10.552(2) Å, c = 25.796(5) Å, beta = 130.51(3) degrees, and Z = 4. The structure consists of monomeric (triethylenetetraaminehexaacetato)neodymate anions, perchlorate anions, sodium cations, and water molecules. The Nd(III) ion adopts a 10-coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…We decided to neglect this contribution for the calculation of NdÀC distances, since, as [7]. In the crystals of the Nd complex [5], the ligand is coordinated to the metal ion in a decadentate fashion via the four N-atoms of the ethylenetriamine backbone and six carboxylate O-atoms, whereas the corresponding Dy 3 complex [7] has one of the acetate groups uncoordinated. Since the average distances of the three carboxylate resonances as determined from the relaxation rates are about the same and in good agreement with those in the crystal structure of [Nd(ttha)] 3À , it can be concluded that the solution-state structure of [Nd(ttha)] 3À is comparable to that in the solid state.…”
Section: Elucidation Of the Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to neglect this contribution for the calculation of NdÀC distances, since, as [7]. In the crystals of the Nd complex [5], the ligand is coordinated to the metal ion in a decadentate fashion via the four N-atoms of the ethylenetriamine backbone and six carboxylate O-atoms, whereas the corresponding Dy 3 complex [7] has one of the acetate groups uncoordinated. Since the average distances of the three carboxylate resonances as determined from the relaxation rates are about the same and in good agreement with those in the crystal structure of [Nd(ttha)] 3À , it can be concluded that the solution-state structure of [Nd(ttha)] 3À is comparable to that in the solid state.…”
Section: Elucidation Of the Coordinationmentioning
confidence: 99%
“…Because of its very small quadrupolar moment, 6 Li has a slow quadrupolar relaxation and, therefore, is a very Fig. 3 (5,15,25,37, and 458). The profiles show significant differences (see Fig.…”
Section: (Ss) (Rr) (Sr) and (Rs) Describe The Arrangement Omentioning
confidence: 99%
“…[5,17] This is different to the La III -TTHA system, where the 1 H and 13 C NMR spectra revealed the existence of only one coordination arrangement around the metal cation in solution. [5] Our results based on the optical properties of Nd III , [8,16] Eu III [17,18] and Ho III [13] complexes with TTHA revealed that species differing in the number of coordinated nitrogen and oxygen atoms, namely [Ln(N 4 3-, are present in the solution for the light and heavy lanthanide ions, respectively. Each of these species may form various stereoisomers, some of which may be op-tically active.…”
Section: Ndmentioning
confidence: 73%
“…The absence of innersphere water molecules for Ln III -TTHA solutions at pH above 3 has been proved by emission spectroscopy [5,6] as well as NMR studies, [7] and was also confirmed in the crystal structures. [8][9][10][11][12][13][14][15][16] Previously, the coexistence of two distinct complexes of Eu III -TTHA in solution over the entire pH range has been reported. [5,17] This is different to the La III -TTHA system, where the 1 H and 13 C NMR spectra revealed the existence of only one coordination arrangement around the metal cation in solution.…”
Section: Ndmentioning
confidence: 99%
“…To the best of our knowledge, the structure of the complexes formed by H 6 TTHA and lanthanide ions had not been studied by X-ray diffraction until 1997. [8] Heteronuclear complexes or coordination polymers formed with this ligand remain elusive. (TTHA)] 2À ions, which result in a one-dimensional chain.…”
Section: Introductionmentioning
confidence: 99%